Unverified information and reconstruction of rumor regulation. (3rd July 2022) - Xudong, Cao; Wenting, Huang
ABSTRACT: Rumor is defined as false information under the framework of Chinese laws, but in practice, law enforcement agencies tend to incorporate unverified information into the regulation of rumor, which broadens the range of enforcement. Unverified information may be subjectively and honestly believed to be true, and it could be false, inaccurate or accurate in an objective manner. In contrast, rumor, circulated with subjective malice, will inevitably lead to objective falsehood. As an important part in the marketplace of ideas, the existence of unverified information can promote the discussion and exchange of thoughts from which facts and truth are derived. Common law and most civil law systems adopt a subjective criterion to judge whether speech can be regarded as legal. This article suggests that China law should adopt the following approach. It should be determined whether the speech is unverified information before further judgment is made. Specifically speaking, speech should be presumed as unverified information rather than rumor if it is not targeted at a specific subject, or it is aimed at a specific subject with public interest involved. Speech deemed as rumor should be curbed, and the rumormongers are punishable, while the dissemination of unverified information shall be restricted if there is objective and obvious inaccuracy but the speaker should not be punished.